Formate-mediated magnetic superexchange in the model hybrid perovskite [(CH3)2NH2]Cu(HCOO)3. Issue 37 (8th September 2020) - Scatena, Rebecca; Johnson, Roger D.; Manuel, Pascal; Macchi, Piero
Abstract : The hybrid-perovskite [(CH3 )2 NH2 ]Cu(HCOO)3 shows antiferromagnetic and ferromagnetic interactions, as predicted by the GKA rules, proven applicable by experimental charge-density analysis. Abstract : We have investigated the magnetic and electronic structures of crystalline dimethylammonium copper formate [(CH3 )2 NH2 ]Cu(HCOO)3, a model compound that belongs to a wide class of hybrid organic–inorganic perovskites. We present the results of a combined experimental approach, where neutron diffraction and magnetisation measurements were used to solve the ground state magnetic structure in which the same ligand mediates both antiferromagnetic and ferromagnetic interactions, while the electron charge density distribution and orbital occupancy were determined by high-resolution X-ray diffraction. The latter enabled a microscopic analysis of the chemical bonding, from which we established a detailed correlation between the structural, electronic, and magnetic properties of [(CH3 )2 NH2 ]Cu(HCOO)3, demonstrating the primary role of Cu–O bonding in establishing the nature of the exchange. Our results elucidate the mechanism of magnetic exchange mediated by formate anions, from which we examine the applicability of foundational theories of purely inorganic perovskites and define characteristics that the ligands should meet to support the use of the Goodenough–Kanamori–Anderson rules.